HAK WARIS ANAK YANG LAHIR DARI PERKAWINAN SIRI - Armansyah Armansyah (Universitas Sriwijaya, 2016)
Every child born of the marriage is entitled to an inheritance from his parents. In this case, the child born of the marriage siri must obtain recognition of her biological father first. To obtain such recognition, invite born from the marriage siri must apply to the judges. Just as in the case of M. Iqbal who is a child born of a marriage between Hj series. Machica Mochtar and H. Moerdiono. From these cases stated in Constitutional Court Decision No. 46 / PUU-VII / 2010 on the Recognition Children Out of Marriage stating that children born of the marriage siri have a relationship nasab with his father if it can be proved with the tools based on technology and science, just cause the child is entitled to a living everyday and costs until she was an adult. The role of the Notary in this case can protect the children born of the marriage siri the deed was borrowed. Keywords: children's inheritance rights, marriage series, the role of the Notary, probate.